The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jcim.2c00236
|View full text |Cite
|
Sign up to set email alerts
|

p38α Kinase Auto-Activation through Its Conformational Transition Induced by Tyr323 Phosphorylation

Abstract: p38α is a key serine/threonine kinase that can enable atypical auto-activation through Zap70 phosphorylation and initiate T cell receptor signaling. The auto-activation plays an important role in autoimmune diseases. Although the classical activation mechanism of p38α has been studied in-depth, the atypical activation mechanism of Y323 phosphorylation-induced p38α auto-activation remains largely unexplained, especially the regulatory effects of phosphorylation on different sites (Y323 vs T180). From the X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Details of the MD simulation was published previously (Li et al, 2019b; Yang et al, 2022; Zang et al, 2022). In brief, the transferable intermolecular potential with three points (TIP3P) water model (Berendsen et al, 1981) was employed to describe the solvent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the MD simulation was published previously (Li et al, 2019b; Yang et al, 2022; Zang et al, 2022). In brief, the transferable intermolecular potential with three points (TIP3P) water model (Berendsen et al, 1981) was employed to describe the solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The three protein structures (RIP1 and RIP3) were geometrically optimized using the conjugate gradient (CG) method and further refined by 100-ns explicit solvent molecular dynamics (MD) simulations using GROMACS 2018.8 (Abraham et al, 2015) and the Charmm36m force field (Huang et al, 2017). Details of the MD simulation was published previously (Li et al, 2019b;Yang et al, 2022;Zang et al, 2022). In brief, the transferable intermolecular potential with three points (TIP3P) water model (Berendsen et al, 1981) was employed to describe the solvent.…”
Section: Modelling and MD Detailsmentioning
confidence: 99%
“…This was followed by constant-temperature equilibration at 310 K for 1.0 ns, with a positional restraint of 10.0 kcal/mol•Å 2 on protein atoms in a canonical ensemble (NVT). Subsequently, an equilibration simulation was performed for 1.0 ns at 1 atm and 310 K in the NPT ensemble with a positional restraint of 4.0 kcal/mol•Å 2 on backbone atoms of the protein [19]. The production MD simulations were carried out at 310 K and 1 atm with a time step of 2.0 fs.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…These conformational differences raise the question of whether their conformational changes to the active conformation occur through similar or different mechanisms. To this end, computational studies have played a significant role in advancing our understanding of this topic. For example, the Roux group has conducted extensive investigations on the conformational change of cSrc, focusing on the transitions between the DFG-in inactive conformation and the active conformation. , Their findings revealed that the A-loop conformational change occur prior to the inward rotation of the αC helix, and both transitions occur with relatively small free-energy barriers. In a separate study, the same group examined DFG flipping in the inactive conformation and compared it with the Abl kinase .…”
Section: Introductionmentioning
confidence: 99%